2021
DOI: 10.1021/acs.estlett.1c00532
|View full text |Cite
|
Sign up to set email alerts
|

Impact of COVID-19 Controls on the Use of Illicit Drugs and Alcohol in Australia

Abstract: Methamphetamine, MDMA, cocaine, cannabis, and alcohol in samples from 20 wastewater treatment plants servicing the eight state or territory capitals of Australia were analyzed, with equivalent coverage of >45% of the national population. Trends in drug consumption were calculated and assessed from samples collected from 2016 to 2020, with a focus on pre-COVID-19 (August 2016 to December 2019), versus February to June 2020, when Australia observed a nationwide lockdown. Results showed delayed but significant de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(18 citation statements)
references
References 14 publications
1
17
0
Order By: Relevance
“…The authors found an increase of 72% in hydrocodone consumption in the latter wastewater collections, but decreases in the consumption of the illicit drugs MAMP and COC, of 16 and 42%, respectively. Bade et al (2021) , evaluated the consumption of MAMP, MDMA, COC, THC, and alcohol through wastewater analysis from 20 WWTP in Australia from February to June 2020, during a national lockdown, and compared the finding with pre-pandemic estimates. The estimates of MAMP consumption presented decreases of up to 50%, but cannabis consumption increased significantly.…”
Section: Resultsmentioning
confidence: 99%
“…The authors found an increase of 72% in hydrocodone consumption in the latter wastewater collections, but decreases in the consumption of the illicit drugs MAMP and COC, of 16 and 42%, respectively. Bade et al (2021) , evaluated the consumption of MAMP, MDMA, COC, THC, and alcohol through wastewater analysis from 20 WWTP in Australia from February to June 2020, during a national lockdown, and compared the finding with pre-pandemic estimates. The estimates of MAMP consumption presented decreases of up to 50%, but cannabis consumption increased significantly.…”
Section: Resultsmentioning
confidence: 99%
“…Many countries around the world were in lockdown, limiting social interaction and large get togethers, and thus, the distribution and consumption of certain drugs were expected to be affected. Recent studies have shown that the restrictions enforced by authorities have influenced the use of illicit drugs and NPS by the population. The only sites involved in this study that were not subject to any restrictions at the time of collection were from New Zealand and sites US3–10.…”
Section: Resultsmentioning
confidence: 99%
“…During the COVID-19 pandemic, WBE has been used for a wide range of applications to explore temporal trends of substance use, self-medication practises and other lifestyle aspects, which may be affected depending on the circumstances caused by the pandemic. In this respect, several major topics are often addressed: alcohol consumption [8] , [9] , [10] , use and production of illicit drugs and new psychoactive substances (NPS) as well as human pharmaceutical consumption patterns [10] , [11] , [12] , [13] , [14] , [15] . In addition, the WBE methodology provides insights beyond questions concerning a given catchment population.…”
Section: Introductionmentioning
confidence: 99%